Total project management of construction safety, health, and environment (T. Telford ; American Society of Civil Engineers, Publications Sales Dept. [distributor], 1995)
This book provides an extensive list of factors that should be considered on all construction related projects, whilst highlighting, with the aid of worked examples, the key areas that will make the most significant contribution to success. It also provides details on the very latest UK legislation. Including the recent CDM Regulations and European Directives, it: provides a framework for the development of pro-active management of Safety, Health and Environment (SHE) in the construction industry; describes a systematic approach to construction SHE management which promotes continuing improvement in SHE performance in all construction activities; and defines the minimum She objectives to be considered during each construction activity.